# Math

posted by Bethany

Loga(x+4) + loga(x-4) = 4

1. Anonymous

lgt(a)+lgt(b)=lgt(a*b)

lgt(x+4)+lgt(x-4)=4

lgt[(x+4)*(x-4)]=4

lgt is the logarithm with base 10.

Antilogarithm of this expresion is

(x+4)*(x-4)=10^4

(x+4)*(x-4)=10.000

x^2+4x-4x-4*4=10.000

x^2-16=10.000

x^2=10.000+16

x^2=10.016

x=sqroot(10.016)

x=100.0799680256

## Similar Questions

1. ### math trouble

I have 2 problems I need help with using either substitution or elimination method what is the solution set of 3x -2y = -4 and 5x = 2y?
2. ### HELP!

I have no idea what the answer to this problem is, I'm given choices but I'm still lost. Given: log sub a 2=.4, log sub a 3 =.5, log sub a 5=.8 what is log sub a .01?
3. ### Algebra help

If loga 8=2.079, loga 5=1.609, and loga 3=1.099, find the following?
4. ### algebra

express as an equivalant expression that is a single logarithmic and simplfy if poissible loga(2x+10)-loga(x^2-25)
5. ### Math - logarithmic equation

Solve the logarithmic equation. Please show all of your work. Loga(x+3) + loga(x-3) = 3
6. ### Math - Properties of Logarithm

Can someone show how to this question. Loga(x+3) + Loga(x-3) = 3 I don't know if I'm typing this correctly the a is the base. So, I'm thinking, Loga((x+3)(x-3)) = 3 (x+3)(x-3) = 3^a x^2 - 9 = 3^a, x^2 = 3^a + 9 x = sqrt(3^a + 9) but …
7. ### math/calculus

solve the equation loga(x-5)- loga (x+9)=loga(x-7)-loga(x+9) all a's are lower please show work